2015
DOI: 10.1016/s0415-6412(15)30070-9
|View full text |Cite
|
Sign up to set email alerts
|

Forever Young(er): potential age-defying effects of long-term meditation on gray matter atrophy

Abstract: While overall life expectancy has been increasing, the human brain still begins deteriorating after the first two decades of life and continues degrading further with increasing age. Thus, techniques that diminish the negative impact of aging on the brain are desirable. Existing research, although scarce, suggests meditation to be an attractive candidate in the quest for an accessible and inexpensive, efficacious remedy. Here, we examined the link between age and cerebral gray matter re-analyzing a large sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, the practice of meditation was found to be positively correlated with fluid intelligence, resilience, and global network efficiency . Moreover, gray matter volume is reported to be preserved in meditators compared to age‐matched controls …”
Section: The Brain As a Target Of Stressmentioning
confidence: 94%
“…Furthermore, the practice of meditation was found to be positively correlated with fluid intelligence, resilience, and global network efficiency . Moreover, gray matter volume is reported to be preserved in meditators compared to age‐matched controls …”
Section: The Brain As a Target Of Stressmentioning
confidence: 94%
“…They found that, in both groups, age-related gray matter decline was present, however the slope the regression line was significantly steeper in controls than in meditators. This indicated that in meditators, the age-related loss of gray matter is less profound than in non-meditators (Luders et al, 2015). On the other hand, it is thought that engaging in mindfulness practices can possibly induce changes as a result of neuroplasticity.…”
Section: Investigated Brain Activity In Experienced Meditatorsmentioning
confidence: 99%
“…There are several studies supporting this idea with evidence. Luders, Cherbuin and Kurth (2015), for example, studied the link between age and whole-brain gray matter in meditators and healthy controls. They found that, in both groups, age-related gray matter decline was present, however the slope the regression line was significantly steeper in controls than in meditators.…”
Section: Investigated Brain Activity In Experienced Meditatorsmentioning
confidence: 99%
“…Following up on these previous findings, three novel cross‐sectional imaging studies were conducted examining whether meditators show less age‐related decline of brain tissue. Study I and study II used MRI and were based on T1‐weighted data obtained on a 1.5‐Tesla scanner. Here, 50 long‐term meditation practitioners (28 men and 22 women) were compared to 50 control subjects (28 men and 22 women).…”
Section: New Research: 2013–2016mentioning
confidence: 99%
“…On average, meditators had close to 18 years of practice (mean (SD): 17.3 (9.8) years; range 5–38 years), where meditation styles included Vipassana, Shamatha, and Zazen. Importantly, within all three studies, meditators and their study‐specific controls were scanned at the same site, using the same scanner, and following the same scanning protocol …”
Section: New Research: 2013–2016mentioning
confidence: 99%